A phenol resin sphere with a carbon nanotube sphere inside, a carbon material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611114329.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-23
AI Technical Summary
但是该发明得到的材料结构强度比较弱,而且抗压抗拉强度也较弱
本发明由于酚醛树脂球内部嵌入了碳纳米管球,其碳化后可提高抗压抗拉强度及导电性能,作为硅碳用多孔碳的前驱体,有利于提高硅碳材料充电膨胀时的抗拉强度,降低硅碳的循环膨胀率,提升硅碳材料的倍率性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical technology. More specifically, it relates to a phenolic resin ball with carbon nanotube spheres inside, carbon materials, their preparation methods, and applications. Background Technology
[0002] The new energy vehicle and large-scale energy storage industries are developing at an unprecedented pace, placing higher demands on the energy density, power density, cycle life, and safety performance of lithium-ion batteries (LIBs). As a core component of lithium-ion batteries, the performance of the anode material directly determines the overall electrochemical performance of the battery. Traditional graphite anode materials, due to their relatively low theoretical specific capacity (372 mAh / g), are gradually failing to meet the stringent energy density requirements of high-end applications. Against this backdrop, silicon (Si)-based materials, with their extremely high theoretical specific capacity (approximately 4200 mAh / g, Li4.4Si alloy), low delithiation potential plateau, and abundant reserves on Earth, are widely recognized as one of the most promising candidates for next-generation high-energy-density lithium-ion battery anode materials. However, silicon-based anodes face two major challenges in practical applications: First, during lithium-ion insertion / extraction, the volume of silicon expands and contracts dramatically (volume change rate > 300%). This enormous mechanical stress leads to electrode material pulverization and detachment, as well as instability and continuous rupture of the solid electrolyte interphase (SEI) film, resulting in rapid capacity decay. Second, silicon's intrinsic electronic conductivity is low, leading to poor rate performance and limiting its application in high-power devices. To overcome these challenges, researchers have developed various strategies, among which combining nano-silicon particles with carbon materials is the most effective and feasible approach to date. Carbon materials not only provide an excellent conductive network to accelerate electron transport but also act as a buffer matrix, effectively suppressing silicon volume expansion and maintaining the integrity of the electrode structure. Among numerous carbon precursors, phenolic resin (PF) has become one of the preferred precursors for preparing high-performance carbon materials due to its wide availability, low cost, high carbonization rate, and ease of controlling structure and pores through molecular design. Therefore, the development of silicon-carbon composite anode materials based on phenolic resin is of vital scientific significance and application value for promoting the commercialization of high-energy-density lithium batteries.
[0003] Phenolic resin (PF), a thermosetting plastic with a long history, is an ideal precursor for preparing high-performance carbon materials (such as activated carbon, glassy carbon, carbon foam, etc.) because its molecular structure is rich in benzene rings and it can form dense, hard glassy carbon with a high char residue after carbonization.
[0004] Since their discovery, carbon nanotubes (CNTs) have attracted widespread attention in the field of composite materials due to their unique tubular hollow structure, extremely high aspect ratio, excellent mechanical properties, and good electrical and thermal conductivity. Introducing CNTs into a carbon matrix to construct CNT / carbon composites is an effective way to improve the performance of traditional carbon materials. In the field of lithium-ion battery anode materials, research on CNT / carbon composites mainly focuses on how to utilize CNTs to construct efficient conductive networks and enhance mechanical support. A common strategy is to physically blend CNTs with carbon sources (such as pitch, phenolic resin, sucrose, etc.) and then prepare composite carbon materials through pyrolysis.
[0005] CN104828804A discloses a method for preparing porous carbon nanotube-carbon spherical composite materials. The method includes: dispersing carbon nanotubes; preparing a resin diluent, adding carbon nanotubes to obtain a uniform suspension, adding a curing agent to obtain a spheroidizing solution; dropping the spheroidizing solution into a layered oil bath for suspension and curing, followed by separation, washing, and drying to obtain composite microspheres; carbonizing and activating the composite microspheres to obtain activated microspheres; and washing and drying the activated microspheres to obtain the porous carbon nanotube-carbon spherical composite material. This invention prepares carbon nanotube-carbon spherical composite materials using a titration method combined with layered oil bath curing. The titration process ensures uniform spherical diameter without the need for grading. The prepared carbon nanotube-carbon spherical composite material has a much higher carbon nanotube content than existing methods, with a wide spherical diameter range, controllable and uniform size, relatively porous microspheres, and excellent activation properties on both the surface and interior of the entire sphere. However, the material obtained by this invention has relatively weak structural strength, as well as weak compressive and tensile strength.
[0006] Research has revealed that when phenolic resin contains only carbon nanotubes and lacks carbon nanotube spheres, the interfacial interaction between the carbon nanotubes and the carbonized phenolic resin carbon is very weak. Under external force, the carbon nanotubes easily detach from the phenolic resin carbon, resulting in a weak structural strengthening effect. Such carbon materials, when used as precursors for silicon-carbon materials, exhibit low initial efficiency and poor cycle performance. Furthermore, when phenolic resin contains neither carbon nanotube spheres nor carbon nanotubes, the carbonized phenolic resin carbon has low strength. Such carbon materials, when used as precursors for silicon-carbon materials, also exhibit low initial efficiency and poor cycle performance. Summary of the Invention
[0007] The technical problem to be solved by this invention is to overcome the defects and deficiencies of the existing technology and provide a phenolic resin ball with carbon nanotube spheres inside, a carbon material, its preparation method and application. The phenolic resin ball has a particle size Dv50 of 3-20 μm, and the carbon nanotube sphere has a particle size Dv50 of 2-19 μm. The phenolic resin completely fills the internal gaps and surface of the carbon nanotube sphere. The mass ratio of carbon nanotube sphere to phenolic resin is 1:1-500. Because the phenolic resin ball is embedded with carbon nanotube sphere, its carbonization can improve its compressive and tensile strength and electrical conductivity. As a precursor of porous carbon for silicon-carbon materials, it is beneficial to improve the tensile strength of silicon-carbon materials during charging expansion, reduce the cycle expansion rate of silicon-carbon materials, and improve the rate performance of silicon-carbon materials.
[0008] The purpose of this invention is to provide a phenolic resin ball with carbon nanotube spheres inside and its preparation method.
[0009] Another objective of this invention is to provide a carbon material and a method for preparing the same.
[0010] Another objective of this invention is to provide the application of carbon nanotube spheres in phenolic resin spheres or carbon material battery electrode materials.
[0011] The above-mentioned objective of this invention is achieved through the following technical solution: A phenolic resin ball with carbon nanotube spheres inside, wherein the particle size Dv50 of the phenolic resin spheres is 3-20 μm, and the particle size Dv50 of the carbon nanotube spheres inside is 2-19 μm, wherein the phenolic resin completely fills the internal gaps and surface of the carbon nanotube spheres, and the mass ratio of the carbon nanotube spheres to the phenolic resin is 1:1-500, preferably 1:1-2.
[0012] Preferably, the carbon nanotube spheres are composed of multi-walled carbon nanotubes with an outer diameter of 5-50 nm and a length ≥20 μm, and the porosity of the carbon nanotube spheres is 30%-99.9%.
[0013] Preferably, the carbon nanotube spheres are one or more combinations of untreated pure multi-walled carbon nanotubes, catalyst-free purified multi-walled carbon nanotubes, or surface-functionalized multi-walled carbon nanotubes, wherein the surface-functionalized carbon nanotubes are modified with -COOH or -OH groups; preferably, the phenolic resin is a Resol-type phenolic resin or a Novolac-type phenolic resin, and its solid content is 30%-35%.
[0014] The method based on the phenolic resin spheres with carbon nanotube spheres as described above includes the following steps: (1) Preparation of carbon nanotube spheres: Select carbon nanotube raw materials, add them to a solvent, and ultrasonically disperse them to form a carbon nanotube dispersion with a concentration of 10-50 g / L and no surfactant; input the dispersion into a spray dryer for spray drying, and collect carbon nanotube spheres with a particle size Dv50 of 2-19 μm after spray drying. (2) Preparation of phenolic resin filling liquid: Select phenolic resin raw materials, add curing agent and diluent, stir evenly, adjust the viscosity of the system to 50-200 mPa·s, and obtain phenolic resin filling liquid; (3) Phenolic resin filling: The carbon nanotube balls prepared in step (1) are added to the phenolic resin filling solution, and the vacuum impregnation method is used to make the phenolic resin filling solution completely penetrate into the internal gaps and surface of the carbon nanotube balls. (4) Curing and molding: Take out the impregnated carbon nanotube balls, remove the excess filling liquid on the surface, and perform gradient curing to obtain the target product.
[0015] Preferably, in step (1), the ultrasonic dispersion power is 100-300W and the dispersion time is 30-60min; the solvent is one or more mixed solvents selected from deionized water, ethanol or N,N-dimethylformamide.
[0016] Preferably, in step (1), the spray drying conditions are controlled as follows: inlet air temperature 150-250℃, outlet air temperature 75-150℃, and spray speed 1 ml / hour-10 tons / hour. More preferably, the inlet air temperature of the spray drying is 190-210℃ and the outlet air temperature is 90-110℃. In step (2), the curing agent is hexamethylenetetramine, and the amount used is 8%-12% of the mass of phenolic resin. The diluent is ethanol or acetone, and the amount used is 20%-40% of the mass of phenolic resin.
[0017] Preferably, in step (3), the vacuum impregnation conditions are: impregnation for 30-90 minutes at a temperature of 25-40℃ and a pressure of -0.08~-0.05MPa, with slow stirring at 50-100r / min during the impregnation process; in step (4), the gradient curing conditions are: pre-curing at 80℃ for 1-2 hours, then heating to 120-150℃ and holding for 2-4 hours, and then cooling to room temperature; the heating rate of the gradient curing is 5-10℃ / min.
[0018] A carbon material is obtained by carbonizing and activating phenolic resin spheres with carbon nanotube spheres as described above. (1) The carbon material has a spherical morphology with an average roundness of 0.65-0.8; (2) The interior of the carbon material is carbon nanotube spheres, the particle size Dv50 of the carbon nanotube spheres is 2-19μm, and the mass ratio of the carbon nanotube spheres to the spherical carbon material is 1:1-300.
[0019] (3) The particle size Dv50 of the carbon material is 3-20 μm; (4) The particle size distribution (Dv90-Dv10) / Dv50 of the carbon material is 0.5-3.0, preferably 0.5-1.5; (5) The specific surface area of the carbon material is 800-3000 m². 2 / g, preferably 1000-2500m 2 / g; (6) The pore volume of the carbon material is 0.2-2.0 cm³. 3 / g, preferably 0.5-1.2cm 3 / g; (7) The average pore size of the carbon material is 0.5-10.0 nm, preferably 1.5-2.0 nm; (8) The compressive strength P of the carbon material is 50MPa≤P≤1200MPa, preferably 100MPa≤P≤1200MPa; A method for preparing the carbon material described above includes the following steps: (1) The phenolic resin ball with carbon nanotube spheres inside as described in any one of claims 1-3 is heated to 500-1000°C at a heating rate of 1-20°C / min under nitrogen protection, and kept at 500-1000°C for 1-10 hours. (2) Under nitrogen protection, the carbon material is naturally cooled to room temperature and then dispersed into carbon material with a particle size Dv50 of 3-20 μm. (3) Add the carbon material from (2) into an atmosphere furnace, introduce nitrogen carrier gas and water vapor or carbon dioxide reaction gas, keep it at 500-1200℃ for 1-20h, and then cool it naturally to room temperature under nitrogen protection. Preferably, the volume ratio of carrier gas to reaction gas is 3~5:1.
[0020] The above-mentioned phenolic resin spheres with carbon nanotube spheres inside or the above-mentioned carbon materials are used in battery electrode materials.
[0021] The present invention has the following beneficial effects: This invention incorporates carbon nanotube spheres embedded within phenolic resin spheres. After carbonization, these spheres can improve compressive and tensile strength as well as electrical conductivity. As a precursor for porous carbon in silicon-carbon materials, this invention helps to improve the tensile strength of silicon-carbon materials during charging expansion, reduce the cycling expansion rate of silicon-carbon materials, and enhance the rate performance of silicon-carbon materials. Detailed Implementation
[0022] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0023] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.
[0024] Example 1 A carbonization and activation carbon material using phenolic resin spheres containing carbon nanotube spheres, the specific steps of which are as follows: Step (1): Preparation of carbon nanotube spheres: Purified multi-walled carbon nanotubes (outer diameter 5-50 nm, length ≥20 μm) were selected as raw materials and added to a mixed solvent of ethanol and deionized water (volume ratio 1:2) to adjust the concentration of carbon nanotube dispersion to 20 g / L; ultrasonic dispersion was performed at 200 W for 45 min to form a uniform carbon nanotube dispersion (without surfactant); the dispersion was fed into a spray dryer, and the inlet air temperature was controlled at 200 ℃, the outlet air temperature at 100 ℃, and the spray speed at 100 mL / h for spray drying. The dried carbon nanotube spheres were collected, with a particle size of 5-8 μm and a porosity of 45%.
[0025] Step (2): Preparation of phenolic resin filling solution: Select Resol type phenolic resin (solid content 32%), add hexamethylenetetramine (10% of the mass of phenolic resin) and ethanol (30% of the mass of phenolic resin), stir evenly, adjust the viscosity of the system to 100 mPa·s, and obtain phenolic resin filling solution.
[0026] Step (3): Phenolic resin filling: The carbon nanotube balls prepared in step (1) are added to the phenolic resin filling solution in step (2) and placed in a vacuum impregnation device. The impregnation temperature is controlled at 30°C, the impregnation pressure is -0.07MPa, and the impregnation time is 60min. During the impregnation process, the mixture is slowly stirred at a speed of 80r / min to ensure that the phenolic resin filling solution completely penetrates into the internal gaps and surface of the carbon nanotube balls.
[0027] Step (4): Curing and molding: Take out the carbon nanotube balls impregnated in step (3), absorb the excess filling liquid on the surface with filter paper, and then perform gradient curing: heat up to 80℃ at a heating rate of 8℃ / min, pre-curing for 1.5h; then heat up to 130℃ and keep warm for 3h for deep curing; finally cool down naturally to room temperature to obtain phenolic resin balls with carbon nanotube balls inside, with a particle size of 6-9μm and a mass ratio of carbon nanotube balls to phenolic resin of 1:1.2.
[0028] Step (5): Carbonization and activation: The phenolic resin spheres with carbon nanotube spheres inside, obtained in step (4), are heated to 750℃ at a heating rate of 10℃ / min under nitrogen protection and held at 750℃ for 6 hours. Under nitrogen protection, they are then naturally cooled to room temperature. The resulting carbon material is dispersed into carbon materials with a particle size Dv50 of 3-20μm. The obtained carbon material is added to an atmosphere furnace, and nitrogen carrier gas and water vapor reaction gas are introduced, wherein the volume ratio of nitrogen to water vapor is 4:1; the gas flow rate is 300 mL / min. After holding at 850℃ for 10 hours, the material is naturally cooled to room temperature under nitrogen protection to obtain the carbon material.
[0029] Step (6): Silicon-carbon composite material: The carbon material from step (5) is placed in a tube furnace and heated from room temperature to 450°C at a rate of 2°C / min in a N2 atmosphere; then the temperature is changed to a mixture of 20% SiH4 and N2 with a gas flow rate of 500 mL / min and maintained at 450°C for 12 h; under nitrogen protection, it is naturally cooled to room temperature to obtain the silicon-carbon composite material.
[0030] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that step (1) is omitted, that is, carbon nanotube spheres are not added. The rest will not be described in detail.
[0031] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that purified multi-walled carbon nanotubes (outer diameter 5-50 nm, length ≥20 μm) are used instead of the comparative carbon nanotube spheres. In step (3), the sphere-forming liquid is dropped into the layered oil bath and suspended and solidified by preparing and preheating the layered oil bath. Then, the spheres are separated, washed and dried in sequence to obtain composite spheres. The specific process conditions are the same as those in Example 1 of CN104828804A. The obtained particle size is within the same range as that in Example 1.
[0032] Methods for testing the electrical conductivity of powder materials: The electrical conductivity of carbon materials was tested using a conductivity meter (Suzhou Jinglü Electronics ST-2255A). Conductivity. A 5g sample of carbon material powder was pressed into a pellet using an electronic press, with a pressure of 5000kg ± 2kg maintained for 20s to obtain a carbon material test sample. This sample was then placed between the electrodes of a conductivity meter, and the resistance R (in Ω) was obtained by applying voltage U and current I across its terminals. The height of the test sample was h (in cm), and the area of the test sample was S = 3.14 cm². 2 The powder conductivity of silicon-carbon material is calculated using the formula δ=h / (S×R), with units of S / cm.
[0033] Crushing force test (Yuaneng Technology SPFT1000) 1. Clean the glass slide, put 5ml of anhydrous ethanol in a small measuring cup, use a toothpick to pick up a little sample and disperse it in the ethanol, shake it to disperse it evenly, then drop three drops into the glass slide, place it in the instrument and clamp it. 2. Locate the particles under a microscope and use the software's built-in particle size calibration function; 3. Record the particle crushing process on video and observe the changes in the stress-strain curve during the test; 4. Observe the crushing of particles after crushing, keep the particle images after the test, generate stress-strain curves, and calculate the crushing force; Electrode and half-cell preparation and electrochemical performance testing: Using the negative electrode materials prepared in the above embodiments and comparative examples as negative electrode active materials, negative electrode sheets were prepared respectively. CR2032 coin cells were fabricated using conventional methods, and the electrical performance of the cells was tested. The specific testing methods are as follows: (1) Half-cell assembly: Assemble CR2032 button cells in a glove box, with lithium metal sheet as counter electrode, polypropylene microporous membrane as separator, and LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC=1:1), wherein the concentration of LiPF6 is 1mol / L. The battery was charged and discharged using the LAND battery testing system; (2) Initial efficiency test: After the CR2032 coin cell was left to stand for 6 hours, it was discharged at 0.1C to 0.005V and the capacity was recorded as Q1; then it was discharged at a constant voltage of 0.005V until the current was cut off at 0.01C and the total capacity was recorded as Q2; after standing for 5 minutes, it was charged at a constant current of 0.1C to 1.5V; the ratio of the initial delithiation capacity to the initial lithium insertion capacity is the initial coulombic efficiency of the battery.
[0034] (3) Electrode expansion rate: After the CR2032 type button cell was left to stand for 6 hours, it was discharged to 0.005 V at 0.05 C, and then discharged to 0.005 V at 0.01 C; then the button cell was disassembled in the glove box, the electrode was cleaned with DEC and the thickness of the electrode was measured; the expansion rate was calculated as: (thickness of electrode in the first fully charged state - thickness of fresh electrode) / thickness of fresh electrode × 100%; Test data of Example 1 and Comparative Examples 1-2: In Example 1, because carbon nanotube spheres are embedded inside the phenolic resin spheres, the conductivity of the carbonized phenolic resin spheres after carbonization, the crushing force of the carbon material obtained after further activation, the first efficiency of silicon-carbon and the expansion rate of the electrode are significantly improved. Specific data are shown in Table 1.
[0035] Table 1
[0036] As shown in Table 1, this invention embeds carbon nanotube spheres within phenolic resin spheres. After carbonization, this improves compressive and tensile strength as well as electrical conductivity. As a precursor for porous carbon in silicon-carbon materials, it helps improve the tensile strength of silicon-carbon materials during charging expansion, reduces the cycling expansion rate of silicon-carbon materials, and enhances the rate performance of silicon-carbon materials. The above embodiments are preferred embodiments of this invention, but the embodiments of this invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of this invention should be considered equivalent substitutions and are included within the protection scope of this invention.
Claims
1. A phenolic resin ball with carbon nanotube spheres inside, characterized in that: The phenolic resin spheres have a particle size Dv50 of 3-20 μm, and the interior is composed of carbon nanotube spheres with a particle size Dv50 of 2-19 μm. The phenolic resin completely fills the internal gaps and surface of the carbon nanotube spheres, and the mass ratio of the carbon nanotube spheres to the phenolic resin is 1:1-500.
2. The phenolic resin ball with carbon nanotube spheres inside as described in claim 1, characterized in that: The carbon nanotube spheres are composed of multi-walled carbon nanotubes with an outer diameter of 5-50 nm and a length of ≥20 μm. The porosity of the carbon nanotube spheres is 30%-99.9%.
3. The phenolic resin ball with carbon nanotube spheres inside as described in claim 1, characterized in that: The carbon nanotube spheres are one or more combinations of untreated pure multi-walled carbon nanotubes, catalyst-free purified multi-walled carbon nanotubes, or surface-functionalized multi-walled carbon nanotubes. The surface-functionalized carbon nanotubes are modified with -COOH or -OH groups. The phenolic resin is a Resol-type phenolic resin or a Novolac-type phenolic resin with a solid content of 30%-35%.
4. A method for preparing phenolic resin spheres with carbon nanotube spheres as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Preparation of carbon nanotube spheres: Select carbon nanotube raw materials, add them to a solvent, and ultrasonically disperse them to form a carbon nanotube dispersion with a concentration of 10-50 g / L and no surfactant; input the dispersion into a spray dryer for spray drying, and collect carbon nanotube spheres with a particle size Dv50 of 2-19 μm after spray drying. (2) Preparation of phenolic resin filling liquid: Select phenolic resin raw materials, add curing agent and diluent, stir evenly, adjust the viscosity of the system to 50-200 mPa·s, and obtain phenolic resin filling liquid; (3) Phenolic resin filling: The carbon nanotube balls prepared in step (1) are added to the phenolic resin filling solution, and the vacuum impregnation method is used to make the phenolic resin filling solution completely penetrate into the internal gaps and surface of the carbon nanotube balls. (4) Curing and molding: Take out the impregnated carbon nanotube balls, remove the excess filling liquid on the surface, and perform gradient curing to obtain the target product.
5. The preparation method according to claim 4, characterized in that: In step (1), the ultrasonic dispersion power is 100-300W and the dispersion time is 30-60min; the solvent is one or more mixed solvents selected from deionized water, ethanol or N,N-dimethylformamide.
6. The preparation method according to claim 4, characterized in that: In step (1), the spray drying conditions are controlled as follows: inlet air temperature 150-250℃, outlet air temperature 75-150℃, and spray speed 1 ml / hour-10 tons / hour. Preferably, the inlet air temperature of the spray drying is 190-210℃ and the outlet air temperature is 90-110℃. In step (2), the curing agent is hexamethylenetetramine, and the amount used is 8%-12% of the mass of phenolic resin. The diluent is ethanol or acetone, and the amount used is 20%-40% of the mass of phenolic resin.
7. The preparation method according to claim 4, characterized in that: In step (3), the vacuum impregnation conditions are: impregnation for 30-90 minutes at a temperature of 25-40℃ and a pressure of -0.08~-0.05MPa, with slow stirring at 50-100r / min during the impregnation process; in step (4), the gradient curing conditions are: pre-curing at 80℃ for 1-2 hours, then heating to 120-150℃ and holding for 2-4 hours, and then cooling to room temperature; the heating rate of the gradient curing is 5-10℃ / min.
8. A carbon material, characterized in that: The phenolic resin spheres with carbon nanotube spheres inside, as described in any one of claims 1-3, are obtained by carbonization and activation. (1) The carbon material has a spherical morphology with an average roundness of 0.65-0.8; (2) The interior of the carbon material is carbon nanotube spheres, the particle size Dv50 of the carbon nanotube spheres is 2-19μm, and the mass ratio of the carbon nanotube spheres to the spherical carbon material is 1:1-300. (3) The particle size Dv50 of the carbon material is 3-20 μm; (4) The particle size distribution (Dv90-Dv10) / Dv50 of the carbon material is 0.5-3.0, preferably 0.5-1.5; (5) The specific surface area of the carbon material is 800-3000 m². 2 / g, preferably 1000-2500m 2 / g; (6) The pore volume of the carbon material is 0.2-2.0 cm³. 3 / g, preferably 0.5-1.2cm 3 / g; (7) The average pore size of the carbon material is 0.5-10.0 nm, preferably 1.5-2.0 nm; (8) The compressive strength P of the carbon material is 50MPa≤P≤1200MPa, preferably 100MPa≤P≤1200MPa.
9. A method for preparing the carbon material according to claim 8, characterized in that, Includes the following steps: (1) The phenolic resin ball with carbon nanotube spheres inside as described in any one of claims 1-3 is heated to 500-1000°C at a heating rate of 1-20°C / min under nitrogen protection, and kept at 500-1000°C for 1-10 hours. (2) Under nitrogen protection, the carbon material is naturally cooled to room temperature and then dispersed into carbon material with a particle size Dv50 of 3-20 μm. (3) Add the carbon material from (2) into an atmosphere furnace, introduce nitrogen carrier gas and water vapor or carbon dioxide reaction gas, keep it at 500-1200℃ for 1-20h, and then cool it naturally to room temperature under nitrogen protection. Preferably, the volume ratio of carrier gas to reaction gas is 3~5:
1.
10. The application of the phenolic resin sphere with carbon nanotube spheres inside as described in any one of claims 1-3, or the carbon material as described in claim 8, in battery electrode materials.
Citation Information
Patent Citations
A preparing method of a porous carbon nanotube-charcoal spherical composite material
CN104828804A